Pieśń o chwale Rzeczypospolitej Obojga Narodów. Uwagi o tradycji genologicznej „Proporca albo Hołdu pruskiego” Jana Kochanowskiego - Banaś-Korniak, Teresa (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The aim of the paper is to show that Jan Kochanowski’s “Proporzec albo Hołd Pruski”, a work of literature considered for a long time to be poor in artistic terms, refers to the convention of a triumphant song of victory, namely the epinikion. It is a literary form with ancient roots. The poet of Czarnolas, in his original way, combined the convention of epinikion with verse-driven canvassing speech (on the border between genus deliberativum and genus demonstrativum), using a number of arguments in favour of implementing the resolutions of the Sejm (Parliament Assembly) of Lublin of 1569. The work consistently develops one thread – the struggle with the Teutonic Knights, which is connected with the selective presentation of the historical images of the Polish rulers’ military campaigns for Pomerania and Duchy of Prussia. The consistency of the presented historical descriptions with the ideological content, expressive “speech decorations” and faithfulness to the conventions of the sixteenth-century political poetry make the literary artistry of Proporzec… impressive and standing out with its artistry against the background of occasional Old Polish poems.
The Song of the Polish-Lithuanian Commonwealth’s Glory. Remarks on the Genological Tradition of “Proporzec albo Hołd Pruski (The Flag or Prussian Homage)” by Jan Kochanowski
Keywords: Polish-Lithuanian Commonwealth; Jan Kochanowski; Proporzec albo Hołd pruski; unia polsko-litewska